Disclosure of human immunodeficiency virus status to children in South Africa: A comprehensive analysis - Sabine L. van Elsland; Remco P.H. Peters; Cornelis Grobbelaar; Patiswa Ketelo; Maarten O. Kok; Mark F. Cotton; A. Marceline van Furth (AOSIS, 2019)
Background: The extent of disclosure of HIV status to children and adolescents and the context facilitating their disclosure process have received little attention. Objectives: To assess disclosure and provide a comprehensive analysis of characteristics associated with disclosure to children (3-14 years) receiving antiretroviral treatment in a South African semi-urban clinic. Methods: This cross-sectional study used structured interview administered questionnaires which were supplemented with medical record data. Predictors included child, caregiver, clinical and socio-economic characteristics, viral suppression, immune response, adherence, health-related quality of life and family functioning. Results: We included 190 children of whom 45 (23.7%) received disclosure about their HIV status, of whom 28 (14.7%) were partially disclosed and 17 (8.9%) were fully disclosed. Older age of the child and higher education of the caregiver were strongly associated with disclosure. Female caregivers, detectable viral load, syrup formulation, protease inhibitor (PI) regimens with stavudine and didanosine, and self-reported non-adherence were strongly associated with non-disclosure. Conclusion: When children do well on treatment, caregivers feel less stringent need to disclose. Well-functioning families, higher educated caregivers and better socio-economic status enabled and promoted disclosure. Non-disclosure can indicate a sub-optimal social structure which could negatively affect adherence and viral suppression. There is an urgent need to address disclosure thoughtfully and proactively in the long-term disease management. For the disclosure process to be beneficial, an enabling supportive context is important, which will provide a great opportunity for future interventions.